Forecasting Financial Markets - Plummer, Tony (Kogan Page, 2012)
Forecasting Financial Markets provides a compelling insight into the psychology of trading behavior and shows how "following the herd" can have disastrous results. It demonstrates how one's ability to make money in the world's financial markets depends critically on an ability to make decisions independently of the crowd.